The system of professions : an essay on the division of expert labor - Abbott, Andrew [Verfasser] (University of Chicago Press, 1988)
"In 'The System of Professions' Andrew Abbott explores central questions about the role of professions in modern life: Why should there be occupational groups controlling expert knowledge? Where and why did groups such as law and medicine achieve their power? Will professionalism spread throughout the occupational world? While most inquiries in this field study one profession at a time, Abbott here considers the system of professions as a whole. Through comparative and historical study of the professions in nineteenth- and twentieth-century England, France, and America, Abbott builds a general theory of how and why professionals evolve." (Verlag, BIBB-Doku)
Keywords: T 4.5 Soziologie; T 4.8 Arbeitswissenschaften; T 1.2 Historische Berufsbildungsforschung; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; Berufssoziologie; Berufsforschung; Arbeitsforschung; Berufsgenese; Rechtsprechung; Arbeitsteilung; Historische Entwicklung; Internationaler Vergleich; Fallbeispiel; England; Frankreich; USA; 19. Jahrhundert; 20. Jahrhundert